Diabetic endothelial microangiopathy and pulmonary dysfunction - Zhang, Lanlan; Jiang, Faming; Xie, Yingying; Mo, Yan; Zhang, Xin; Liu, Chuntao (Frontiers in Endocrinology, 2023)
Type 2 diabetes mellitus (T2DM) is a widespread metabolic condition with a high global morbidity and mortality rate that affects the whole body. Their primary consequences are mostly caused by the macrovascular and microvascular bed degradation brought on by metabolic, hemodynamic, and inflammatory variables. However, research in recent years has expanded the target organ in T2DM to include the lung. Inflammatory lung diseases also impose a severe financial burden on global healthcare. T2DM has long been recognized as a significant comorbidity that influences the course of various respiratory disorders and their disease progress. The pathogenesis of the glycemic metabolic problem and endothelial microangiopathy of the respiratory disorders have garnered more attention lately, indicating that the two ailments have a shared history. This review aims to outline the connection between T2DM related endothelial cell dysfunction and concomitant respiratory diseases, including Coronavirus disease 2019 (COVID-19), asthma, chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF).